Synthesis of p-Nitrobenzenediazoamido Black 10B and Its Application to Spectrophotometric Determination ofMicro Amount of Cadmium - Zhang, Peng-Fei; Gao, Hong-Wen (Asian Journal of Chemistry, 2010)
A new azoamino reagent p-nitrobenzenediazoamido black 10B (p-NDABB) has been synthesized, and found to be a good chromogenic reagent for cadmium. In pH 9.8 Na2B4O7-NaOH buffer solution cadmium reacts with p-NDABB to form green chelate (1 : 3), exhibiting an absorptivity 1.81 x 105 L mol–1 cm–1. Beer's law is obeyed in the range 0–9 μg/25 mL Cd(II). The method is simple and rapid, with high sensitivity and good selectivity and it is applied to the determination of trace amounts of cadmium in waste water and industrial materials with satisfactory results.